Effect of Organizational Justice on Budget Slack: the Role of Budget Emphasis as a Moderating Variable - Maulidinsyah, Teuku; Fahlevi, Heru; Syam, Fazli (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of organizational justice on budget slack, along with the moderating role of budget emphasis in the functional relationship between these two variables. The study sample includes 366 officer from local government units in the province of Aceh, Indonesia. Data collection was conducted through questionnaires, and the data analysis model employed moderated regression analysis. The findings reveal that organizational justice has a significant and negative impact on budget slack. Moreover, budget emphasis not only exhibits a negative influence on budget slack but also moderates the impact of organizational justice on budget slack. The negative influence of organizational justice on budget slack increases with the rise in budget emphasis.